Characterizing the Bladder's Response to Onabotulinum Toxin Type A Using a Rat Model. Issue 6 (November 2016) - Dieter, Alexis A.; Wu, Jennifer M.; Siddiqui, Nazema Y.; Degoski, Danielle J.; Brooks, Jillene M.; Dolber, Paul C.; Fraser, Matthew O.
Abstract : Objectives: The aim of this study was to characterize the response of the rat bladder neuromuscular system to intramural injection of onabotulinum toxin type A (BoNT/A) over 9 weeks using in vivo cystometry (CMG) and in vitro contractility (IVC). Methods: Chronic bladder catheters were implanted in female Sprague-Dawley rats, and either (1) BoNT/A (10 units in 20 μL saline) or (2) saline (20 μL) was injected in 5 × 4 μL doses throughout the bladder wall. At 1, 3, 6, and 9 weeks after injection, conscious restrained CMG was performed. At each time point, 25% of each group (8 BoNT/A and 4 controls) was euthanized and bladders harvested for IVC. We measured IVC in response to electric field stimulation, carbachol, and potassium chloride. Results: In total, 47 animals were included; 31 underwent BoNT/A injection, and 16 received sham (saline). Bladder capacities did not differ significantly between groups for each time point. One week after injection BoNT/A animals exhibited significantly longer bladder contraction durations and lower voiding efficiencies compared with controls. By 3 weeks these values returned to control levels. For BoNT/A animals, contractile response to carbachol stimulation was enhanced at 3 weeks. Otherwise, there were no differences in IVC responses. Conclusions: One week after BoNT/A injection, prolonged bladder contractions are noted in rats. This may reflect supraspinal compensation for denervation by increasing the duration of efferent drive during voiding. After 3 weeks postinjection, we observed no differences in either CMG or IVC responses suggesting either compensatory efferent sprouting, increased gap junction formation, or loss of BoNT/A effect. Abstract : In response to Botulinum Toxin Type A injection, the detrusor smooth muscle in a rat model exhibits changes in voiding parameters with no change in functional tissue contractile response.